The relationships between acetylcholine-induced chest pain, objective measures of coronary vascular function and symptom status - Miner, Steven E. S.; McCarthy, Mary C.; Ardern, Chris I.; Perry, Chris G. R.; Toleva, Olga; Nield, Lynne E.; Manlhiot, Cedric; Cantor, Warren J. (Frontiers in Cardiovascular Medicine, 2023)
Acetylcholine-induced chest pain is routinely measured during the assessment of microvascular function.The aim was to determine the relationships between acetylcholine-induced chest pain and both symptom burden and objective measures of vascular function.In patients with angina but no obstructive coronary artery disease, invasive studies determined the presence or absence of chest pain during both acetylcholine and adenosine infusion. Thermodilution-derived coronary blood flow (CBF) and index of microvascular resistance (IMR) was determined at rest and during both acetylcholine and adenosine infusion.Patients with epicardial spasm (>90%) were excluded; vasoconstriction between 20-90% was considered endothelial dysfunction.Eighty-seven patients met the inclusion criteria. Of these 52 patients (60%) experienced chest pain during acetylcholine while 35 (40%) did not. Those with acetylcholine-induced chest pain demonstrated:1) Increased CBF at rest (1.6± 0.7 vs 1.2 ± 0.4, p=0.004)2) Decreased IMR with acetylcholine (Acetylcholine-IMR=29.7±16.3 vs 40.4±17.1, p=0.004), 3) Equivalent IMR following adenosine (Adenosine-IMR: 21.1±10.7 vs 21.8±8.2, p=0.76) 4) Increased adenosineinduced chest pain (40/52 =77% vs 7/35 = 20%, p<0.0001),5) Increased chest pain during exercise testing (30/46 = 63% vs 4/29 = 12%, p<0.00001) with no differences in exercise duration or electrocardiographic changes, and 6) Increased prevalence of epicardial endothelial dysfunction (33/52 = 63% vs 14/35 = 40%, p=0.03).After excluding epicardial spasm, acetylcholine-induced chest pain is associated with increased pain during exercise and adenosine infusion, increased coronary blood flow at rest, decreased microvascular resistance in response to acetylcholine and increased prevalence of epicardial endothelial dysfunction. These findings raise questions about the mechanisms underlying acetylcholine-induced chest pain.